Pengembangan LKPD Berbasis Masalah untuk Meningkatkan Minat Belajar Peserta Didik Kelas IV Tahun Pelajaran 2023/2024 - Putri Zudhah Ferryka; Yuliana Yuliana; Delta Ramawati (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This research aims to determine the characteristics of LKPD based on mathematical sentences, determine the feasibility of LKPD products, and determine students' interest in learning after implementing LKPD based on math sentence problems in chapter 11 class IV. This type of research is Development Research (Research and Development) using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model and the resulting product is a mathematical sentence-based LKPD. This research involved 22 class IV students at SD Negeri 1 Pasung. The feasibility of the LKPD is tested with validation from expert practitioners, media and materials. Data collection used in this research was interviews, observations, questionnaires, tests and documentation. The interview sheet is used to analyze the needs of educators and students before preparing the product. The results of this research concluded that the LKPD has attractive design characteristics, diverse character traits, problem presentation in the form of dialogue, problem presentation stages that are in accordance with the PBL model, presentation of material in the form of videos and games. The feasibility of this LKPD is declared appropriate and not revised, because it is in accordance with the quality indicators of the LKPD content, media, materials and illustrations. Students' interest in learning increased by 41% after using this mathematical sentence problem-based worksheet.